STRATEGI PEMBELAJARAN BAHASA ARAB MENGGUNAKAN MODEL PEMBELAJARAN TEMATIK - Auia Qatrinnada; suparmanto suparmanto; dedi hariadi; Aulia Abdiana; Fira Lutfiana (Armala, 2022)
As we know that learning will not be optimal if there is no learning strategy because the learning strategy is an operational method, it will include the style that the teacher uses in composing lessons, the arts that are displayed by the teacher in the learning process as well as facilities and media in various forms for the learning process, and Learning strategies can be a major factor in the success of language learning.One example of in supporting Arabic learning, the thematic model is one solution. The curriculum K- 13 at the elementary school level gives birth to an eye that is mixed into a single unit, namely thematic. Learning Arabic thematic model is a method that refers to the themes in the environment around students. And the thematic learning aims to develop the competence of attitudes, knowledge, and skills of students. Especially in learning Arabic, it can create a comfortable and pleasant classroom atmosphere, build cohesiveness with each other such as forming cooperative groups, collaborations, study groups, can encourage students to solve problems, Learners can quickly and timely obtain information. In carrying out learning with the thematic model, it must be in accordance with the principles and foundations in accordance with what has been described based on the socialization of the 2013 curriculum provided by the Ministry of Education and Culture.